Adequation of the therapeutic profile, co-morbidities and personal habits of Brugada patients with ICD and its link to dysrhythmic events - Fernandes, Diogo Filipe de Almeida Ferreira (2018)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina